A new insight into manufacturing fine-grained heavy retaining rings. (5th August 2016) - Wang, Zhenhua; Ning, Xiaozhi; Meng, Qing; Sun, Shuhua; Fu, Wantang
Abstract: Heavy retaining rings in electric generators are manufactured from high nitrogen CrMn austenitic steels. It is difficult to product fine-grained heavy retaining rings because of their large size and the stable austenitic matrix. Cold expansion is necessary for the production of heavy retaining rings. In this study, the feasibility of cold expansion followed by annealing for manufacturing fine-grained heavy retaining rings was investigated. 18Mn18Cr0.6N steel was cold tensioned to 10–40% and then annealed at 900–1000 °C. Microstructures were observed using electron backscatter diffraction and mechanical properties were measured using tensile test and hardness test. The preferred nucleation sites of static recrystallization were triple junctions and grain and twin boundaries. After two cycles of 40% cold tension and annealing at 1000 °C, the grain size number changed from 1.5 to 8.5. Cold tensioned texture was completely eliminated through static recrystallization. Through the two-cycle process, the yield and ultimate strength, the linear strain hardening rate, and the hardness were enhanced significantly. Cold expansion followed by annealing is a suitable method for manufacturing fine-grained heavy retaining rings. In addition, detailed nucleation mechanisms of static recrystallization at triple junctions, at the recrystallization front, and between two strained grains were discussed, respectively. Graphical abstract: Highlights: After two cycles of 40% cold tension and annealing, the grain size number changed from 1.5 to 8.5. The strength, the linear strain hardening rate, and the hardness were enhanced significantly. Cold expansion followed by annealing is a suitable method for manufacturing fine-grained heavy retaining rings. Nucleation mechanisms of static recrystallization were given.